On performance trade-offs in cognitive networks - Stathakis, E; Schrammar, N; Rasmussen, L K; Skoglund, M (2010 IEEE International Conference on Wireless Information Technology and Systems, 2010)
In this paper we employ the recently proposed deterministic framework (Avestimehr et al.) to model and analyze cognitive networks. Despite its simplicity, this model captures fundamental aspects of networks and allows explicit calculation of the capacity of multicast relay networks. The performance results we obtain and the conclusions that we draw in the deterministic field can provide useful insights that can be applied on the analysis of Gaussian networks.